Functional nonredundancy of elephants in a disturbed tropical forest. Issue 5 (16th June 2017) - Sekar, Nitin; Lee, Chia‐Lo; Sukumar, Raman
Abstract: Conservation efforts are often motivated by the threat of global extinction. Yet if conservationists had more information suggesting that extirpation of individual species could lead to undesirable ecological effects, they might more frequently attempt to protect or restore such species across their ranges even if they were not globally endangered. Scientists have seldom measured or quantitatively predicted the functional consequences of species loss, even for large, extinction‐prone species that theory suggests should be functionally unique. We measured the contribution of Asian elephants ( Elephas maximus ) to the dispersal of 3 large‐fruited species in a disturbed tropical moist forest and predicted the extent to which alternative dispersers could compensate for elephants in their absence. We created an empirical probability model with data on frugivory and seed dispersal from Buxa Tiger Reserve, India. These data were used to estimate the proportion of seeds consumed by elephants and other frugivores that survive handling and density‐dependent processes (Janzen‐Connell effects and conspecific intradung competition) and germinate. Without compensation, the number of seeds dispersed and surviving density‐dependent effects decreased 26% ( Artocarpus chaplasha ), 42% ( Careya arborea ), and 72% ( Dillenia indica ) when elephants were absent from the ecosystem . Compensatory fruit removal by other animals substantially ameliorated these losses. For instance, reductions in successful dispersal of D. indica were as low as 23% when gaur ( Bos gaurus ) persisted, but median dispersal distance still declined from 30% ( C. arborea ) to 90% ( A. chaplasha ) without elephants. Our results support the theory that the largest animal species in an ecosystem have nonredundant ecological functionality and that their extirpation is likely to lead to the deterioration of ecosystem processes such as seed dispersal. This effect is likely accentuated by the overall defaunation of many tropical systems.